ANALISIS KINERJA SIMPANG TIGA TAK BERSINYAL JALAN RAYA THAMRIN-JALAN RAYA DIPONEGORO, KECAMATAN LAWANG, KABUPATEN MALANG - Servan, Albertus Servan Belawa; Andy Kristafi Arifianto; M. Sa'dillah (Jurnal Qua Teknika, 2025)
Malang District is a growing area in Java with a high population. Lawang sub-district has 111,440 residents with a growth of 0.31% in Malang Regency. Intersections are areas where roads intersect, and road intersections are prone to accidents. Research on the unsignalized triple intersection at Jalan Raya Thamrin - Jalan Diponegoro aims to understand the characteristics and find solutions to the problems in the area. Primary and secondary data were gathered through firsthand observation in the field. Data analysis was conducted to determine the pattern and size of the intersection in accordance with the surrounding environmental conditions.